Following young people with perinatal HIV infection from adolescence into adulthood: the protocol for PHACS AMP Up, a prospective cohort study. Issue 6 (9th June 2016) - Tassiopoulos, Katherine; Patel, Kunjal; Alperen, Julie; Kacanek, Deborah; Ellis, Angela; Berman, Claire; Allison, Susannah M; Hazra, Rohan; Barr, Emily; Cantos, Krystal; Siminski, Suzanne; Massagli, Michael; et al.
Abstract : Introduction: The first generation of adolescents born with HIV infection has reached young adulthood due to advances in treatment. It is important to continue follow-up of these individuals to assess their long-term medical, behavioural and mental health and ability to successfully transition to adulthood while coping with a chronic, potentially stigmatising condition. To accomplish this, and to maintain their interest in long-term research participation, we need to accommodate the changing lifestyles and interests of young adult study participants while ensuring valid data collection. We report the protocol for Pediatric HIV/AIDS Cohort Study (PHACS) Adolescent Master Protocol (AMP) Up, a prospective cohort study enrolling young adult participants for long-term follow-up. Methods and analysis: AMP Up is recruiting 850 young men and women 18 years of age and older—600 perinatally HIV-infected and a comparison group of 250 perinatally HIV-exposed, uninfected—at 14 clinical research sites in the USA and Puerto Rico. Recruitment began in April 2014 and is ongoing, with 305 participants currently enrolled. Planned follow-up is ≥6 years. Data are collected with a flexible hybrid of online and in-person methods. Outcomes include: transition to adult clinical care and retention in care; end-organ diseases; malignancies; metabolic complications; sexually transmitted infections; reproductive health; mental health and neurocognitive functioning; adherence to antiretroviral treatment; sexual behaviour and substance use; hearing and language impairments; and employment and educational achievement. Ethics and dissemination: The study received ethical approval from the Harvard T.H. Chan School of Public Health's institutional review board (IRB), and from the IRBs of each clinical research site. All participants provide written informed consent; for cognitively impaired individuals with legally authorised representatives, legal guardian permission and participant assent is obtained. Findings will be disseminated through peer-reviewed journals, conference presentations and participant summaries.